A DC to 25 GHz 6‐bit digital attenuator based on 0.18 μm SiGe BiCMOS technology. Issue 8 (1st May 2021) - Hao, Dongning; Zhang, Wei; Liu, Xiubo; Liu, Yanyan
Abstract: A wideband, low phase variation 6‐bit digital step attenuator (DSA) is presented. To further expand the operation bandwidth while keeping low attenuation and phase error, modified π/T‐type attenuator structures are introduced. In the large attenuation unit, the modified π‐type attenuator structure is adopted, which includes middle adjusting capacitance and bypass compensating capacitance. Moreover, the reduced T‐type structure with bypass compensation capacitance is used in the small attenuation units. The influence of the introduced capacitance on various attenuation units is analyzed. To prove the effectiveness of the modified structure on extending the bandwidth, a DSA with a broad bandwidth of DC‐25 GHz and low attenuation and phase error is realized in a 0.18 μm SiGe BiCMOS technology. The attenuation range of the attenuator is 31.5 dB with 0.5‐dB step, which is controlled by 6 bits digital input. Its root‐mean‐square (RMS) attenuation error is lower than 0.3 dB, and the phase error (RMS) is below 4.9°. The insertion loss is lower than 11 dB, and the core area is 0.33 mm 2 .